Integrated evaluation of soil nutrients in modern agricultural demonstration garden of Dongyang county - LÜ Su-dan; WANG Guang-yu; WU Ya-lang; SHI Zhou; WANG Ke (浙江大学学报. 农业与生命科学版, 2002)
In this paper, with the application of GIS, the spatial database and attribute database were established. Integrated evaluation of soil nutrients were studied with five indexes of organic matter, available N, available P, available K and pH with the method of correlation analysis and main factor analysis. S-typed and parabola-type function were developed according to their effect on plant, and the function values were also calculated. The weight value for the nutrient index was calculated respectively. Finally, the IFI (integrated fertility index) using the two methods was calculated. The results are similar. The dispersed data can transform the continuous polygon data through interpolation method with kriging. The rank mapping of soil nutrition was produced with ARCVIEW software.